Lineage diversity and reproductive modes of the Daphnia pulex group in Chinese lakes and reservoirs - Ma, Xiaolin; Petrusek, Adam; Wolinska, Justyna; Hu, Wei; Yin, Mingbo (Molecular phylogenetics and evolution, 2019)
Recent studies of the distribution and diversity of freshwater zooplankton have indicated that the previously understudied Eastern Palearctic region is an important biogeographic hotspot. Here, we explored the lineage diversity and reproductive modes of the Daphnia pulex species group across China. Members of this group are often keystone species of standing water bodies and are frequently used as a model system for ecological, evolutionary and, more recently, genomic studies. We found members of the D. pulex group in seven of seventy-six Chinese water bodies examined. We analyzed their phylogenetic position using mitochondrial markers, and explored the genetic structure of six populations using microsatellite markers. Mitochondrial DNA analysis suggested the presence of two distinct species complexes in China: the D. pulex complex that has a global distribution, and an apparently endemic Eastern Palearctic D. mitsukuri complex. Microsatellite analyses of six populations suggested that three of these reproduced by cyclical parthenogenesis, as evidenced by high clonal diversity and the absence of deviations from the Hardy-Weinberg equilibrium. In contrast, three other populations showed remarkably low diversity of multilocus genotypes. This suggests an obligate parthenogenetic reproductive mode, which was confirmed in one of the populations by comparison of genotypes of Daphnia adults and dormant embryos. All presumably obligate parthenogenetic clones were heterozygous at the majority of microsatellite loci, suggesting their hybrid origin. This was further supported by analyses of a small GTPase nuclear gene (rab4), as two alleles within single individuals belonged to different clades. Interestingly, one putatively obligate parthenogenetic clone carried three distinct alleles suggesting higher ploidy and potential gene flow between the D. pulicaria and D. mitsukuri complexes. Our data show that the expansion of the D. pulex complex in the Eastern Palearctic was associated with widespread hybridization.
Keywords: Animals; rozmnožování; Geography; DNA, Mitochondrial; jezera; China; Reproduction; Daphnia; Genes, Mitochondrial; pravděpodobnostní funkce; zeměpis; Genetic Variation; Likelihood Functions; Phylogeny; Haplotypes; mitochondriální geny; mitochondriální DNA; Principal Component Analysis; Čína; Microsatellite Repeats; Lakes; analýza hlavních komponent; zvířata; haplotypy; fylogeneze; genetická variace; mikrosatelitní repetice